2004
DOI: 10.1016/j.pbiomolbio.2003.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Calsequestrin and the calcium release channel of skeletal and cardiac muscle

Abstract: Calsequestrin is by far the most abundant Ca(2+)-binding protein in the sarcoplasmic reticulum (SR) of skeletal and cardiac muscle. It allows the Ca2+ required for contraction to be stored at total concentrations of up to 20mM, while the free Ca2+ concentration remains at approximately 1mM. This storage capacity confers upon muscle the ability to contract frequently with minimal run-down in tension. Calsequestrin is highly acidic, containing up to 50 Ca(2+)-binding sites, which are formed simply by clustering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
323
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(347 citation statements)
references
References 150 publications
23
323
1
Order By: Relevance
“…We also examined the expression level of key regulators of the E-C coupling process in TA muscle. By using quantitative RT-PCR, we measured the mRNA level of the ␣ 1 , ␤ 1 , and ␥ 1 subunits of the voltage-sensing DHPR (Cacna1s, Cacnb1, and Cacng1), the SR Ca 2ϩ release channel type 1 ryanodine receptor (RyR1), type 1 and 2 SERCA pumps (Atp2a1, Atp2a2), and calsequestrin 1 and 2 (Casq1, Casq2), which encode the major Ca 2ϩ -buffering proteins in the lumen of striated muscle SR (23). In 5-week-old-mice, we found that Cacnb1 and Cacng1 mRNAs were significantly increased by 1.3-and 3-fold, respectively, whereas transcript level of Casq2 was decreased by about 30% (Fig.…”
Section: Absence Of Myotubularin Leads To Dysregulation Of Genes Invomentioning
confidence: 99%
“…We also examined the expression level of key regulators of the E-C coupling process in TA muscle. By using quantitative RT-PCR, we measured the mRNA level of the ␣ 1 , ␤ 1 , and ␥ 1 subunits of the voltage-sensing DHPR (Cacna1s, Cacnb1, and Cacng1), the SR Ca 2ϩ release channel type 1 ryanodine receptor (RyR1), type 1 and 2 SERCA pumps (Atp2a1, Atp2a2), and calsequestrin 1 and 2 (Casq1, Casq2), which encode the major Ca 2ϩ -buffering proteins in the lumen of striated muscle SR (23). In 5-week-old-mice, we found that Cacnb1 and Cacng1 mRNAs were significantly increased by 1.3-and 3-fold, respectively, whereas transcript level of Casq2 was decreased by about 30% (Fig.…”
Section: Absence Of Myotubularin Leads To Dysregulation Of Genes Invomentioning
confidence: 99%
“…The SR is the main storage site of intracellular calcium, storing Ca 2ϩ up to 20 mM while maintaining the free SR Ca 2ϩ concentration at ϳ1 mM (2,3). The SR storage capacity enables the muscle cell to continuously contract without diminishing the Ca 2ϩ available for each contraction-relaxation cycle.…”
mentioning
confidence: 99%
“…It is a highly acidic protein with over 50 Ca 2ϩ binding sites, which are formed by the clustering of two or more negatively charged residues. The molecular weight of the CASQ monomer is 40 kDa; and is capable of polymerizing in response to increasing Ca 2ϩ concentrations (Ͼ1 mM) (3). CASQ locates near the ryanodine receptor and attaches to it, via direct interaction or through anchoring by triadin and junctin.…”
mentioning
confidence: 99%
“…Sarcoplasmic reticulum (SR) 3 is a major Ca 2ϩ storage reservoir in muscle. The SR Ca 2ϩ release channel, ryanodine receptor (RyR), forms a large macromolecular complex with transmembrane, luminal, and cytoplasmic components (1).…”
Section: Calsequestrin (Csq) the Major Intrasarcoplasmic Reticulum Cmentioning
confidence: 99%